2013
DOI: 10.3109/07388551.2013.793650
|View full text |Cite
|
Sign up to set email alerts
|

Monocot chimeric jacalins: a novel subfamily of plant lectins

Abstract: Monocot chimeric jacalins are a small group of lectins (currently with nine members), each typically consisting of a dirigent domain and a jacalin-related lectin domain. This unique module structure, along with their limited taxonomic distribution and short time window in molecular evolution, makes them a novel family of lectins. Recent studies have shown that these proteins play important roles in plant stress responses and development. Our knowledge of these proteins in functional domain and evolution has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Although lectins from plants and other species have been an important topic of research for years, most studies dealt with the identification and expansion of a particular lectin family in one species, or specifically focused on one type of lectin motif and its distribution in the plant kingdom [27,28,29,30,31,32,33,34,35,36]. To date, there have only been a few publications that report on the distribution of multiple lectin motifs across plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Although lectins from plants and other species have been an important topic of research for years, most studies dealt with the identification and expansion of a particular lectin family in one species, or specifically focused on one type of lectin motif and its distribution in the plant kingdom [27,28,29,30,31,32,33,34,35,36]. To date, there have only been a few publications that report on the distribution of multiple lectin motifs across plant species.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years many jacalin-related lectin genes have been associated with disease resistance, abiotic stress signaling, wounding, insect damage, or multiple stresses (Song et al 2014). Structural analyses indicated that Hfr-1 and Ta-JA1 share similar three-dimensional structures with other jacalin-related proteins, such as wheat vernalization-related gene 2 (Ver2), wheat chemically induced gene-1(WCI-1), and maize beta-glucosidase-aggregating factor (BGAF) (Ma 2014). …”
Section: Jacalin-like Proteins With Dirigent Domainmentioning
confidence: 99%
“…In contrast the mannose-specific lectins are synthesized without a signal peptide and accumulate in the nucleocytoplasmic compartment of the plant cell. Many mannosespecific jacalin-related domains are linked to a disease response or dirigent domain, thus forming another group of AB-type proteins (Ma 2014). All proteins of this type reported so far have exclusively been found in the Poaceae family.…”
Section: Jacalin-like Proteins With Dirigent Domainmentioning
confidence: 99%
See 2 more Smart Citations